A Retrospective Examination of Home PCA Use and Parental Satisfaction With Pediatric Palliative Care Patients. (March 2022) - Grossoehme, Daniel H.; Brown, Miraides; Richner, Gwendolyn; Zhou, Sarah M.; Friebert, Sarah
Introduction: Home Patient-Controlled Analgesia (PCA) is an effective and often preferred therapy for the treatment of chronic pain symptoms in the pediatric palliative care patient. There is little previous research of patient experience with Home PCA. The purpose of this study was to investigate use of home PCA devices in pediatric patients to inform palliative care providers considering an alternative management option for the treatment of end-of-life or chronic pain. Methods: A chart review was performed of patients prescribed home PCA. Surveys were sent to patients' guardians/caregivers. Questions referred to caregiver impression/satisfaction with information provided regarding use of the PCA machine, the medication used, the benefits and risks of PCA, monitoring of patient pain level and alertness, machine efficacy, and fears and concerns. Results: Thirty-four patients met inclusion criteria, and 18 patient families completed surveys. Demographic data showed that the majority were Caucasian and had a cancer diagnosis. Patient age and duration of home PCA use varied greatly. Overall, participants were satisfied with information received and felt positively about home PCA, albeit expressing concerns. The majority described the machine as easy to use and were satisfied with their child's pain management and level of alertness. Conclusion: Responses indicated that home PCA is a manageable and effective alternative to traditional analgesic medications for management of chronic pain in the pediatric patient.